Synthesis of azulenyl-substituted gold(I)-carbene complexes and investigation of their anticancer activity - Dietl, Martin C.; Hüßler, Christopher; Scherr, Matthias; Frederiksen, Zoé M.; Graf, Jürgen; Rominger, Frank; Rudolph, Matthias; Caligiuri, Isabella; Tripodi, Laura; Rizzolio, Flavio; Scattolin, Thomas; Hashmi, A. Stephen K. (RSC Advances, 2025)
The direct and atom economic synthesis of azulenyl-substituted gold(I) carbene complexes, based on the modular template synthesis using gold(I) isonitrile complexes and amine nucleophiles, is presented. First, two azulenyl-substituted isonitriles as ligands were synthesized from a functionalizable azulene derivative, the latter stemming from a gold-catalyzed dimerization of internal alkynes. These azulene-bound gold(I) isonitrile complexes allow the smooth nucleophilic attack by both aliphatic and aromatic amines. The newly synthesized azulene-substituted gold(I) carbene complexes were evaluated for in vitro anticancer activity against multiple human cancer cell lines. Six lead compounds demonstrated potent and selective cytotoxicity, exceeding that of cisplatin by at least an order of magnitude in resistant and aggressive cancer models. Structure-activity relationship analysis revealed that specific ligand modifications, such as the position of the azulene moiety tethered to the carbene unit or nitrogen-bound ethyl or cyclic groups, are critical for enhancing the anticancer activity.